Pain is common after sexual assault and posttraumatic arousal/reactivity symptoms mediate the development of new or worsening persistent pain. Issue 1 (January 2022) - Short, Nicole A.; Tungate, Andrew S.; Bollen, Kenneth A.; Sullivan, Jenyth; D'Anza, Teresa; Lechner, Megan; Bell, Kathy; Black, Jenny; Buchanan, Jennie; Reese, Rhiannon; Ho, Jeffrey D.; Reed, Gordon D.; et al.
Abstract : Abstract: Clinically significant new or worsening pain (CSNWP) is a common, yet often overlooked, sequelae of sexual assault. Little is known regarding factors influencing the development of CSNWP in sexual assault survivors. The current study used data from a recently completed prospective study to evaluate whether posttraumatic alterations in arousal and reactivity in the early aftermath of sexual assault influence the transition from acute to clinically significant new or worsening persistent pain. Women ≥ 18 years of age (n = 706) presenting for emergency care after sexual assault to 13 emergency care sites were enrolled in the study. Women completed assessments at the time of presentation as well as at 1 week (n = 706, 100%) and 6 weeks (n = 630, 91%). Nearly 70% of women reported CSNWP at the time of emergency care (n = 475, 69%), which persisted to 6 weeks in approximately 2 in 5 survivors (n = 248, 41%). A structural equation model adjusted for age, race, past trauma exposure, and preassault pain levels suggested that posttraumatic alterations in arousal/reactivity symptoms 1 week after assault partially mediated the transition from acute to persistent CSNWP. A significant portion (41%) of women sexual assault survivors develop CSNWP 6 weeks postassault. Posttraumatic arousal/reactivity symptoms in the early aftermath of assault contribute to CSNWP development; such symptoms are potential targets for secondary preventive interventions to reduce chronic postassault pain. Abstract : Early posttraumatic stress symptoms, particularly alterations in arousal and reactivity, mediated the transition from acute to persistent pain among 706 women presenting for emergency care after sexual assault.